Integrated identification of key immune related genes and patterns of immune infiltration in calcified aortic valvular disease: A network based meta-analysis - Wu, Li-Da; Xiao, Feng; Sun, Jin-Yu; Li, Feng; Chen, Yu-Jia; Chen, Jia-Yi; Zhang, Jie; Qian, Ling-Ling; Wang, Ru-Xing (Frontiers in Genetics, 2022)
Background: As the most prevalent valvular heart disease, calcific aortic valve disease (CAVD) has become a primary cause of aortic valve stenosis and a major health problem. We aimed to illustrate roles of immune related genes (IRGs) and immune infiltration in pathogenesis of CAVD. Methods: We used Integrative meta-analysis of expression data (INMEX) to incorporate multiple gene expression datasets related to CAVD. By matching the differentially expressed genes (DEGs) to IRGs from ImmPort database, differentially expressed immune related genes (DEIRGs) were screened out. Biological functional enrichment analysis were conducted based on GO database, KEGG database, DisGeNET database and TRRUST database. Then, we constructed protein–protein interaction (PPI) network and identified the key DEIRGs of CAVD according to the mixed character calculation results. Moreover, CIBERSORT was performed to explore the patterns of immune cells infiltration in CAVD. Finally, using Spearman method, correlation analysis between key IRGs and infiltrating immune cells was conducted. Results: 220 DEIRGs were identified, and the enrichment analysis of DEIRGs showed that they were significantly enriched in inflammatory responses. PPI network was constructed based on DEIRGs and PTPN11, GRB2, SYK, PTPN6 and SHC1 were identified as key IRGs. Compared with normal aortic valve tissue samples, the proportion of neutrophils, T cells CD4 memory activated and macrophages M0 was significantly elevated in calcified aortic valves tissue samples, as well as reduced infiltration of monocytes and NK cells activated. Furthermore, IRGs identified in the present study, including PTPN11, GRB2, PTPN6, SYK, and SHC1, was significantly correlated with the infiltration of various immune cells. Conclusions: This study suggested that PTPN11, GRB2, PTPN6, SYK, and SHC1 might be key IRGs associated with immune infiltration, which play a pivotal role in pathogenesis of CAVD.